ANALYSIS OF STUDENTS MATHEMATICAL REASONING BASED ON FIELD DEPENDENT AND FIELD INDEPENDENT COGNITIVE STYLES - Wahyu Arianto; Sudirman Sudirman; Tjang Daniel Chandra (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aims to describe studentâ€™s mathematical reasoning based on Field Dependent and Field Independent cognitive styles on the material equations and inequalities of the linear absolute value of one variable. This research is a descriptive research with a qualitative approach. The subjects of this research were 4 students of class XI IPA 6 SMA Negeri 1 Sumberpucung with the category of 2 students Field Dependent and 2 students Field Independent. Collecting data in this study is the GEFT test, mathematical reasoning tests, interviews, and documentation. The results showed that students with the Field Dependent on the indicators put forward assumptions about writing down information on the problem using verbal sentences. In the indicator of doing mathematical manipulation students use illustrative images and their own understanding based on questionâ€™s information to solve problems correctly. However, on absolute value inequalities, Field Dependent students made mistakes in making mathematical sentences. This affects indicator drawing conclusions from a statement. On the indicator of checking the validityÂ arguments, student tend not to re-check their answers. Meanwhile, students with the Field Independent on the indicator put forward the conjecture of writing down information on the problem using mathematical sentences. In the indicators of doing mathematical manipulation, Field Independent students use the concept of absolute value to solve problems. For indicators to draw conclusions from a statement Field Independent students are classified as able to draw conclusions correctly and re-check the answers obtained on the indicators to check the validity of the arguments.Keywords: mathematical reasoning, cognitive style, field dependent, field independent